Communication—Formation of Porous Cu3Sn by High-Temperature Current Stressing. (1st January 2016) - Lin, C. K.; Chen, Chih; Chu, David T.; Tu, K. N.
Abstract : Cu3 Sn is a compound commonly formed in solder joints on Cu. In this study, two different Cu3 Sn structures were observed at different stages of current stressing. A normal layer-type and pore-less Cu3 Sn structure was obtained at the current density of 2.27 × 10 4 A/cm 2 at 222°C after 12 h. However, a porous Cu3 Sn structure was formed under the same current stressing conditions after 22 h. The formation of porous Cu3 Sn is explained by the mechanisms of phase transformation and reaction. The porous Cu3 Sn structure is frequently observed in Cu/solder/Cu microbumps with a reduced solder height after electromigration tests.